Elevated adropin: A candidate diagnostic marker for myocardial infarction in conjunction with troponin-I - Aydin, Suna; Kuloglu, Tuncay; Aydin, Suleyman; Kalayci, Mehmet; Yilmaz, Musa; Cakmak, Tolga; Eren, Mehmet Nesimi (Elsevier Science Inc, 2014)
Myocardial infarction (MI; heart attack) can cause injury to or death of heart muscle tissue (myocardium) owing to prolonged ischemia and hypoxia. Troponins and CK-MB are released from heart muscle cells during MI. It has been demonstrated that energy expenditure is regulated by adropin expressed in the endocardium, myocardium, and epicardium. We hypothesized that adropin is released into the bloodstream during myocardial muscle injury caused by MI, so the serum level rises as myocytes die. Therefore, we examined the association between adropin expression and myocardial infarction in isoproterenol-induced myocardial infarction. Rats were randomly allocated to six groups. After treatment they were decapitated and their blood and tissues were collected for adropin measurement. Changes in adropin synthesis in rat heart, kidney and liver tissues in isoproterenol (ISO)-induced MI were demonstrated immunohistochemically. Serum adropin concentrations were measured by ELISA, and troponin-I, CK and CK-MB concentrations by autoanalysis. The results demonstrated that cardiac muscle cells, glomerular, peritubular and renal cortical interstitial cells, hepatocytes and liver sinusoidal cells all synthesize adropin, and synthesis increased 1-24 h after MI except in the liver cells. The findings elucidate the pathogenesis of MI, and the gradual increase in serum adropin could be a novel diagnostic marker and serve as an alternative to troponin-I measurement for diagnosing MI. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Myocardial infarction; Adropin; Cardiac muscle cells; Hepatocytes; Kidneys